2022
DOI: 10.21203/rs.3.rs-1442476/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic influences on neurodevelopmental disorders and their overlap with co-occurring conditions in childhood and adolescence: A meta-analysis.

Abstract: A systematic understanding of the aetiology of neurodevelopmental disorders (NDDs), their co-occurrence, and co-occurrence with other conditions during childhood and adolescence remains incomplete. This meta-analysis bridges gaps in our knowledge. First, we meta-analysed the literature on the relative contribution of genetic and environmental factors to NDDs. Second, we considered the literature on the overlap between different NDD categories. Lastly, we synthesized the literature on the co-occurrence between… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Moreover, the lack of evidence of transdiagnosticity from GWAS should be considered with caution, given the small sample size for neurodevelopmental disorders (particularly learning disorders)­ and meta‐analytic evidence indicating large genetic correlations between most neurodevelopmental disorders 56 . Indeed, cross‐disorder genetic correlation estimates clearly show that there are substantial shared common genetic risks (e.g., across ADHD and ASD) and therefore future studies of specific SNPs that are implicated in multiple disorders will need to be identified through multi‐disorder analyses 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the lack of evidence of transdiagnosticity from GWAS should be considered with caution, given the small sample size for neurodevelopmental disorders (particularly learning disorders)­ and meta‐analytic evidence indicating large genetic correlations between most neurodevelopmental disorders 56 . Indeed, cross‐disorder genetic correlation estimates clearly show that there are substantial shared common genetic risks (e.g., across ADHD and ASD) and therefore future studies of specific SNPs that are implicated in multiple disorders will need to be identified through multi‐disorder analyses 32 .…”
Section: Discussionmentioning
confidence: 99%